Effects of Pyruvate Kinase M2 (PKM2) Gene Deletion on Astrocyte-Specific Glycolysis and Global Cerebral Ischemia-Induced Neuronal Death - Beom-Seok Kang; Bo-Young Choi; A-Ra Kho; Song-Hee Lee; Dae-Ki Hong; Min-Kyu Park; Si-Hyun Lee; Chang-Juhn Lee; Hyeun-Wook Yang; Seo-Young Woo; Se-Wan Park; Dong-Yeon Kim; et al. (MDPI AG, 2023)
Ischemic stroke is caused by insufficient blood flow to the brain. Astrocytes have a role in bidirectionally converting pyruvate, generated via glycolysis, into lactate and then supplying it to neurons through astrocyte-neuron lactate shuttle (ANLS). Pyruvate kinase M2 (PKM2) is an enzyme that dephosphorylates phosphoenolpyruvate to pyruvate during glycolysis in astrocytes. We hypothesized that a reduction in lactate supply in astrocyte PKM2 gene deletion exacerbates neuronal death. Mice harboring a PKM2 gene deletion were established by administering tamoxifen to Aldh1l1-CreERT2; PKM2f/f mice. Upon development of global cerebral ischemia, mice were immediately injected with sodium l-lactate (250 mg/kg, i.p.). To verify our hypothesis, we compared oxidative damage, microtubule disruption, ANLS disruption, and neuronal death between the gene deletion and control subjects. We observed that PKM2 gene deletion increases the degree of neuronal damage and impairment of lactate metabolism in the hippocampal region after GCI. The lactate administration groups showed significantly reduced neuronal death and increases in neuron survival and cognitive function. We found that lactate supply via the ANLS in astrocytes plays a crucial role in maintaining energy metabolism in neurons. Lactate administration may have potential as a therapeutic tool to prevent neuronal damage following ischemic stroke.